Mental Workload Assessment Software in Spanish Language: Development and Validation - Barajas Bustillos, Manuel Alejandro; Maldonado-Macías, Aide Aracely; Hernandez Arellano, Juan Luis (2020)
Mental workload assessment is a complex construct that requires effective software solutions that enables the application of a group of techniques in Spanish language. As methods, the Quality Function Deployment (QFD) is used to translate customer needs into technical requirements for software development. A case-based methodology is used for software design and a usability assessment is conducted. Client’s requirements were established from ergonomists and a software application is designed. According to the System Usability Scale (SUS), the software present good usability indicators. The results obtained were statistically validated by the Wilcoxon test.